Case Report: Immune checkpoint inhibitor-associated myocarditis in an esophageal cancer patient with myasthenia gravis following combined radiotherapy and immunotherapy - Ren, Xue; Yang, Defu; Xu, Ying; Yan, Ying (Frontiers in Oncology, 2026)
Myocarditis associated with immune checkpoint inhibitors is a rare but potentially fatal immune-related adverse event. Esophageal cancer patients with myasthenia gravis, who are recommended to receive radiotherapy combined with immunotherapy, are at risk for ICI-related myocarditis. We report a 69-year-old male esophageal cancer patient with myasthenia gravis who was diagnosed with immune checkpoint inhibitor related myocarditis after receiving radiotherapy combined with immunotherapy. The patient’s laboratory test results showed elevated troponin and N-terminal pro-B-type natriuretic peptide. Electrocardiography revealed arrhythmia and complete left bundle branch block. Despite treatment with methylprednisolone, the patient’s condition was severe, and clinical and auxiliary examination symptoms continued to deteriorate, leading to his unfortunate demise. In this case, the adverse event of myocarditis induced by radiotherapy combined with immunotherapy in oncology patients with myasthenia gravis is an area that requires further investigation. Clinicians must carefully weigh the potential benefits and risks when considering this combined treatment approach and closely monitor patients for adverse events.